Ativação mecanoquímica para obtenção da Zeólita ZSM-5 hierárquica e aplicação na pirólise do plástico - Queiroz, Pedro Filipe Alves Chaves de (2023)
Hierarchical zeolites are materials with a combination of micropores, mesopores, and macropores designed to facilitate the diffusion of bulky molecules while maintaining the characteristics of the original microporous zeolite. Hydrothermal synthesis employs solvent, heat, and time, resulting in higher costs and waste generation. Thus, this research aims to bypass hydrothermal synthesis by utilizing mechanochemical synthesis through the ball milling technique of NH4ZSM-5 zeolite, solvent-free, in conjunction with co-templates: cetyltrimethylammonium bromide (CTMABr) and tetrapropylammonium bromide (TPABr). The grinding time, diameter and number of balls and the rotation scale were optimized to identify the best operational conditions of the ball mill (IKA ULTRA TURRAX TUBE DRIVE – UTTD), for mechanochemical activation of the ZSM-5 zeolite. Data analysis involved X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, and Scanning Electron Microscopy (SEM) coupled with Energy-Dispersive X-ray Spectroscopy (EDS). These analyses revealed that the optimal conditions for the ball mill involved employing fifteen steel balls with 6 mm in diameter without the use of solvents. Textural Analysis (N2 Adsorption and Desorption) indicated that only five minutes were necessary to significantly alter the structure and chemical composition, resulting in reorganization through recrystallization and new bonds generated by the silicate and aluminate groups of the catalysts. Data from thermogravimetric analysis of zeolites underscored the importance of templates in intercrystalline mesopore development. The modified catalysts were applied in the pyrolysis of polypropylene and the products were analyzed by gas chromatography coupled to mass spectrometry (GC/MS). It was observed that the zeolite ZSM-5 with mechanochemical activation produced 94% by mass of compounds in the range of hydrocarbons in the range of C7 to C10, similar to gasoline and diesel, with selectivity for mono-aromatic compounds, showing that the material was obtained effective for the production of high value-added sustainable fuels from the conversion of plastics.